Psychological treatments in the usual clinical practice - Labrador, Francisco Javier; Fernández, Paola; Ballesteros, Francisco (Anales de Psicología / Annals of Psychology, 2011)
The aim of the study is to characterize psychological interven-tion in the usual clinical practice as opposed to the research’s context. The characteristics of a sample of 122 patients asking for psychological help at the Unit of Clinical Psychology in the Complutense University of Madrid, are presented. Patients are mainly women (68.85 %), and the average age is 32.17 years. After identifying the kind of problems for witch the help is required, the length of treatments is considered, clustered in three catego-ries: 20 sessions of treatment or less (32.79 %), between 21 and 34 ses-sions of treatment (31.15 %) and over 34 session (36.60 %). Also the treatment’s length is considered according to the psychopathological diagnosis. Post-traumatic stress disorder and Distimic disorder are the diagnosis witch required a greater number of sessions, whereas generalized anxiety disorder or depressive disorder are those that least sessions re-quired. The generalization of results and it’s implications for the profes-sion clinical practice, and for training clinical psychologists, are discussed.